Development of Innovative Ethno-Vlog Media Based on Ethno-STEM to Equip Students' Creativity and Realize UNNES Conservation Vision - Sudarmin Sudarmin; Langlang Handayani; Sarwi Sarwi; Risa Dwita Hardianti; Norma Eralita; Woro Sumarni; Fonny Dameaty Hutagalung (Journal of Innovation in Educational and Cultural Research, 2024)
This research is essential for the realization of (a) the vision of Universitas Negeri Semarang (UNNES) as a conservation-minded university and (b) the character of student creativity in the global era. This research aims to develop ethno-vlog learning media based on ethno-STEM to realize the UNNES vision of conservation and student creativity. This research is a development study that uses the Thiagarajan model. The resulting product is an innovative STEM-based ethno-vlog media developed through the stages of definition, design, development, and dissemination. The research subjects are students taking ethnoscience and local wisdom courses in the Integrated Science Study Program. As a result of the research data analysis and discussion, the data obtained during the study can be analyzed qualitatively and quantitatively. The analysis of the research data and discussion can be concluded that (a) the Ethno-vlog product has been produced by students taking Ethno-science courses and local intelligence with interesting categories; (b) the student's conservation character and creativity can be developed with the creation and learning of a STEM-based Ethno-vlog project; and (c) students' responses to the tasks of the STEM-based Ethno-vlog project are in good categories. The results of developing this ethno-vlog media can provide students with knowledge about local wisdom for science learning. Additionally, it encourages students to be more caring and actively participate in preserving culture and the environment through innovative educational methods, supporting the conservation vision of Universitas Negeri Semarang (UNNES).